2017
DOI: 10.1080/1120009x.2017.1389807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vancomycin initial dosing on time to systemic inflammatory response syndrome resolution in patients with methicillin-resistant Staphylococcus aureus bacteremia

Abstract: Current guidelines suggest using vancomycin-loading doses for complicated infections despite a lack of evidence to support this practice. To address this gap, we performed a single-centre cohort study of 124 patients with sepsis due to methicillin-resistant Staphylococcus aureus bacteremia. Patients were allocated into two groups based on initial dose of vancomycin, <20 mg/kg or ≥20 mg/kg, and evaluated for time to resolution of systemic inflammatory response syndrome (SIRS). Among a cohort of 124 patients, 87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The clinical failure rate of around 40% in each group is consistent with failure rates documented in other studies using trough-based vancomycin dosing for the treatment of MRSA bacteremia [2022]. Although a few analyses have assessed the impact of PK determined loading doses on day 1 AUC or trough target attainment, only one study has assessed the impact of loading doses on outcomes [2326]. Wesolek and colleagues [26] performed a retrospective cohort study to evaluate the impact of initial vancomycin doses on resolution of systemic inflammatory response syndrome (SIRS) criteria in patients with sepsis secondary to MRSA bacteremia.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The clinical failure rate of around 40% in each group is consistent with failure rates documented in other studies using trough-based vancomycin dosing for the treatment of MRSA bacteremia [2022]. Although a few analyses have assessed the impact of PK determined loading doses on day 1 AUC or trough target attainment, only one study has assessed the impact of loading doses on outcomes [2326]. Wesolek and colleagues [26] performed a retrospective cohort study to evaluate the impact of initial vancomycin doses on resolution of systemic inflammatory response syndrome (SIRS) criteria in patients with sepsis secondary to MRSA bacteremia.…”
Section: Discussionsupporting
confidence: 78%
“…Although a few analyses have assessed the impact of PK determined loading doses on day 1 AUC or trough target attainment, only one study has assessed the impact of loading doses on outcomes [2326]. Wesolek and colleagues [26] performed a retrospective cohort study to evaluate the impact of initial vancomycin doses on resolution of systemic inflammatory response syndrome (SIRS) criteria in patients with sepsis secondary to MRSA bacteremia. Patients who received a first dose of vancomycin ≥ 20 mg/kg ( n = 37) experienced resolution of SIRS criteria within 67 h, on average, compared to 109 h in patients receiving first doses of vancomycin < 20 mg/kg ( n = 87) and Cox proportional hazard modeling showed a faster resolution of SIRS in the first dose ≥ 20 mg/kg group [HR = 1.72 (1.09–2.73)].…”
Section: Discussionmentioning
confidence: 99%
“…Initial regimen It is recommended to use a loading dose of 30 mg/kg (actual body weight) [ 55 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 ] (II). However, there are few safety-related data regarding loading doses of >3 g [ 193 ].…”
Section: Resultsmentioning
confidence: 99%
“…[23] However, in several clinical practice guidelines published in Japan and the United States, loading dose is recommended for seriously ill patients with suspected MRSA infection (eg, those with sepsis, meningitis, pneumonia, or infective endocarditis). [4,6] Several studies [16,21] reported better clinical outcomes in patients treated with vancomycin loading dose. However, due to the lack of large size samples and well-controlled design, these studies were not enough to confirm the efficacy and safety of vancomycin loading dose.…”
Section: Discussionmentioning
confidence: 99%